Measurement of Plasma Parameters by using Nitrogen gas - Al- Shatravi, Ali Gehad (University of Thi-Qar Journal of Science, 2014)
In this work the diode planer magnetron sputtering device was used. This device consists from two alumina disc (8cm) diameter and (5mm) thick. The distance between two electrodes is 2cm, 3cm, 4cm and 5cm. Design and construction double probe made from tungsten wire with (0.1mm) diameter and (1.2mm) length, to investigate electron temperature, electron density and ion density under different distance between cathode and anode measured. The probes were situated in the center of plasma between anode and cathode. The result of this work shown that, when the distance between cathode and anode increased, the electron temperature will decreased. The electron density was found to increase with increasing distance between the electrodes. The behavior of ions density is similar to that electron but the value is higher.